The Role of Cold Water Immersion as a Post-Exercise Recovery Method for Recreational Athlete Based on Creatine Kinase and Vertical Jump: A Randomised Trial - Nurmansyach, Febianto; Sudarsono, Nani Cahyani; Yusra, Yusra (Proceedings Book of International Conference and Exhibition on The Indonesian Medical Education Research Institute, 2022)
Background: Recreational sports have a positive influence on health. However, there will be a concern if the training intensity and volume increase without proper recovery. Cold water immersion has been known as one of the post-exercise recovery methods. Assessment of creatine kinase and vertical jump can be used to monitor the condition of post-exercise recovery. Aim: To evaluate the role of cold water immersion based on creatine kinase and vertical jump. Method: Twenty subjects were randomized to the cold water immersion or passive recovery group. Creatine kinase and vertical jump were measured as a baseline, followed by fatigue protocol (circuit training in gym) and recovery protocol according to each group. The creatine kinase and vertical jump were monitored in three consecutive periods; post-exercise recovery, 24-hour, and 48-hour post-exercise. The mean difference within groups and between groups of creatine kinase and the vertical jump was analyzed using repeated Anova + post-hoc Bonferroni test and T-test, respectively. Results: The intervention group showed faster recovery than the control group at 24-hour post-exercise based on vertical jump. Intervention group had higher vertical jump (p = 0,039) at 24-hour assessment. The intervention group showed faster recovery at 48-hour post-exercise than the control group on creatine kinase. There were also lower (p <0,01) creatine kinase in the intervention group at 48-hour post-exercise measurement. Conclusion: The use of cold water immersion is recommended as a post-exercise recovery method for the recreational athlete after high-volume and high-intensity training.